Sistem Informasi Pendataan Alat Bantu bagi Penyandang Disabilitas pada Dinas Sosial Aceh - Firji, Fajar Adista; Ihsanuddin; Suswati, Dewi (Computer Journal, 2024)
One of the agencies that still relies on manual information systems using Microsoft Word and Excel for its data management is the Aceh Social Services, specifically in handling the Data Management System for Assistive Devices for Persons with Disabilities. This manual process results in delays in report preparation, as it requires the opening of numerous folders and files to gather the necessary data for reports requested by the leadership. The objective of this study is to analyze and design a Web-based Information System for the Management of Assistive Devices for Persons with Disabilities at the Aceh Social Services. Two methods were used to collect data: field studies and literature reviews. Based on observations, it can be concluded that managing the data for assistive devices using an online system is more efficient, especially with the specific reporting features for assistive devices. The system was developed using web-based programming languages such as PHP, HTML, CSS, JavaScript, and MySQL as its database.